'Are we all secular/ized yet?': reflections on David Goldberg's 'Are we all post-racial yet?'. Issue 13 (20th October 2016) - Fadil, Nadia
ABSTRACT: This paper expands upon some of Goldberg's initial reflections regarding the new type of 'subject' that is at the heart of post-raciality. A particular attention is paid to the connection with religion, as many of the current conflicts in Europe have been articulated through the grammar of secularism and religion, especially in relationship to Islam. This observation invites us to consider how this 'racialization of religion' figures as a reminder of the central role of this politico-theological question in the demarcation of who counts as a proper (political) subject, and how the current debates about Islam figure as a reminder of that.